(18)F-FCWAY, a serotonin 1A receptor radioligand, is a substrate for efflux transport at the human blood-brain barrier - Liow, Jeih-San; Zoghbi, Sami S; Hu, Shuo; Hall, Matthew D; Hines, Christina S; Shetty, H Umesha; Araneta, Maria D; Page, Emily M; Pike, Victor W; Kreisl, William C; Herscovitch, Peter; Gottesman, Michael M; et al. (NeuroImage (Orlando, Fla.), 2016)
Efflux transporters at the blood-brain barrier can decrease the entry of drugs and increase the removal of those molecules able to bypass the transporter. We previously hypothesized that (18)F-FCWAY, a radioligand for the serotonin 5-HT1A receptor, is a weak substrate for permeability glycoprotein (P-gp) based on its very early peak and rapid washout from human brain. To determine whether (18)F-FCWAY is a substrate for P-gp, breast cancer resistance protein (BCRP), and multidrug resistance protein (MRP1) - the three most prevalent efflux transporters at the blood-brain barrier - we performed three sets of experiments. In vitro, we conducted fluorescence-activated cell sorting (FACS) flow cytometry studies in cells over-expressing P-gp, BCRP, and MRP1 treated with inhibitors specific to each transporter and with FCWAY. Ex vivo, we measured (18)F-FCWAY concentration in plasma and brain homogenate of transporter knockout mice using γ-counter and radio-HPLC. In vivo, we conducted positron emission tomography (PET) studies to assess changes in humans who received (18)F-FCWAY during an infusion of tariquidar (2-4mg/kg iv), a potent and selective P-gp inhibitor. In vitro studies showed that FCWAY allowed fluorescent substrates to get into the cell by competitive inhibition of all three transporters at the cell membrane. Ex vivo measurements in knockout mice indicate that (18)F-FCWAY is a substrate only for P-gp and not BCRP. In vivo, tariquidar increased (18)F-FCWAY brain uptake in seven of eight subjects by 60-100% compared to each person's baseline. Tariquidar did not increase brain uptake via some peripheral mechanism, given that it did not significantly alter concentrations in plasma of the parent radioligand (18)F-FCWAY or its brain-penetrant radiometabolite (18)F-FC. These results show that (18)F-FCWAY is a weak substrate for efflux transport at the blood-brain barrier; some radioligand can enter brain, but its removal is hastened by P-gp. Although (18)F-FCWAY is not ideal for measuring 5-HT1A receptors, it demonstrates that weak substrate radioligands can be useful for measuring both increased and decreased function of efflux transporters, which is not possible with currently available radioligands such as (11)C-loperamide and (11)C-verapamil that are avid substrates for transporters.